Descriptive analysis of gamification in educational projects chemistr.io: chemical bonding specialized game - Mat Zaid, Muhammad Afham Fakhri; Che Rahimi, Che Azim Hakimi; Muhamad Nizam, Anwar Razeeq; Mat Russ, Nazirah; Mohd Ali, Noor Saadiah; Jamaudin, Rosmaya (CFS IIUM, 2024)
The gamification approach has gained significant traction as an effective way to engage students in learning across various educational levels and disciplines, including chemistry. Chemistry, in particular, is often perceived as a challenging subject due to its intricate concepts and the need to understand their interconnections. This study addresses the challenges faced by learners, especially pre-university students, in grasping abstract chemical bonding theories through traditional pedagogical methods. Thus, a mobile game-based called Chemistr.io was developed and incorporated with assessment that tailored with one of the topics in Physical Chemistry, namely Chemical Bonding. The gamification approach was evaluated based on overall feedback towards the gamification element of Chemistr.io quantitatively, using a 5-point numerical rating scale. The data collected from 67 students taking Chemistry I in Semester 2, 2023/2024 were then analysed descriptively using mean value. The overall mean score of students’ perception towards gamification in learning chemistry is ranging from 4.59 to 4.78. The results revealed that students engaged in these gamification activities demonstrated positive and a deeper grasp of the subject matter. Incorporating gamification into Chemistry could leverage motivation and critical thinking in the subject matter. The Chemistr.io mobile game can be commercialized further and serve as an interactive learning module for Physical Chemistry subjects.